(untitled) (Economics and region, 2023)
The article analyses the results of a survey of senior pupils regarding their awareness of financial issues and involvement in financial transactions in order to assess the level of financial literacy and financial inclusion. For this, statistical methods of processing the results of an online survey, which contained fifteen questions, were used. It was found that only a quarter of the respondents studied economic disciplines at school, and almost half of the respondents do not want to take financial literacy courses in the future, in particular, due to the lack of practical orientation. The age of the respondents has a positive effect on the level of their financial literacy and financial inclusion. From 75 to 90% of senior pupils already use banking services and can name from two to ten domestic financial institutions. Loans, insurance, deposits, and settlements/payments were expected to be the most well-known financial services for respondents, but a third of senior pupils did not name any of them. As for the ability to manage money, almost 16% of respondents already place their pocket money into an account instead of spending it. It was found that 85.4% of senior pupils have financial goals, which they plan to achieve by finding additional opportunities to earn money, as well as by reducing expenses or receiving additional income from savings. At the same time, only about 13% of respondents are constantly involved in family budget planning, and almost 20% of them have never participated in it. Increasing the level of financial literacy and financial inclusion of senior pupils is possible due to the creation of a special financial mobile application that would take into account the preferences of young people.